Effectiveness of Foliar Application of Potassium on Flowering and Fruiting of Cocoa - Rudy Erwiyono; Achmad Sucahyo; Suyono .; Sugeng Winarso (Indonesian Coffee and Cocoa Research Institute, 2006)
An experiment of foliar application of potassium on cocoa has been carried out in Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute in Jember to study its effectiveness on the flowering and fruiting of cocoa. The experiment was arranged according to factorial design of 2 factors with environmental design of randomized complete blocks. The first factor was soil application of potassium fertilization in two levels, i.e. without fertilizer and with K-fertilizer as KCl. The second factor was application of potassium from two sources, i.e. KCl and KNO 3 , with 3 levels, i.e. without fertilizer (sprayed with water only), K-fertilizer as KCl and K-fertilizer as KNO 3. The experiment was done in 4 replicates. Parameters observed included newly formed flowers, new young fruits and the fresh-developing fruits. The results showed that foliar application of fertilizer was more effective than soil application and plant response was better in increasing new flower formation. On the other hand, the effect of soil application of fertilizer was slow. Foliar application of potassium followed by soil application of potassium fertilizer was more effective in the form of KNO 3 rather than in the form of KCl in increasing new flower formation. The dosage of foliar application of potassium could not significantly increase new young fruit formation. On the other hand, the dosage of soil application of potassium could increase new young fruit formation significantly. Key words: foliar application, kalium, flower, young fruit, cocoa.